Incidental news exposure and opinion leader’s role in spreading climate change information and environment-friendly behavior on social media - Rachela Belinda Fatharani (Universitas Negeri Yogyakarta, 2023)
Social media is the primary medium for disseminating information, including global topics such as climate change. The topic of climate change is related to the community's application of environmentally friendly habits. Social media and social media users have their characteristics in disseminating information about climate change compared to other media. Social media allows a user to be accidentally exposed to the information referred to as incidental news exposure. In addition, in disseminating information, opinion leaders have a role in disseminating information to social media users. This study aims to determine the role of opinion leaders and incidental news exposure in disseminating information about climate change. This research is a case study involving fourteen participants divided into two Focused-Group Discussion (FGD) groups. After carrying out the FGD, the results of the participants' discussions were analyzed using the diffusion of innovation theory, in which there are elements of the spread of an innovation consisting of the innovation, communication channel, time, and social system. The study results show that incidental news exposure and opinion leaders play a role in disseminating information about climate change and environmentally friendly habits. Incidental news exposure and opinion leaders can be part of disseminating information with the diffusion of innovation theory approach.